MODERN HYDRAULIC FLUIDS “VPO “VOLGOHIMNEFTJ” - S. A. Chumakov (Литьë и металлургия)
The issue of expediency of application of fire-safe hydraulic fluids on the basis of working experience of foreign and domestic furnaces is examined. The brief review of assortment of hydraulic fluids produced by “VPO VolgohimneftJ ” is given.